(untitled) (Jurnal AbdiMas Nusa Mandiri, 2024)
The development of Financial Accounting Standards has changed in line with business development. On June 30, 2021 DSAK endorsed the SAK for Private Entities (SAK EP), which will be effective January 1, 2025 replacing the SAK for Entities Without Public Accountability (SAK ETAP). Accounting education has a role in the successful implementation of SAK in Indonesia. IAI West Java helped socialize the new SAK to SMK teachers throughout West Java. The aim of this activity is the accounting teachers are expected to get an overview of the SAK EP and obtain references of this topic. The socialization method includes lectures as a material delivery technique, questions and discussions as a form of increasing and developing the potential of professional teachers. Based on the results of the socialization participants’ responses, it was found that the implementation and usefulness indicators showed a very good category, this shows that the socialization activities were carried out very well and this activity contributed benefits to participants in enriching accounting knowledge, especially related to the latest SAK. The aim of the activity has been achieved very well, namely increasing the teachers’ knowledge about the latest information relating to the latest financial accounting standards (Private Entity SAK).